Optimal depth of electromyographic endotracheal tube: A novel approach using video laryngoscopy. Issue 10 (24th August 2022) - Lin, Yu-Chun; Lin, Ming-Chih; Lin, Wen-Chun; Shen, Ching-Hui
Abstract : Background: Electromyographic (EMG) endotracheal tubes with surface electrodes are used during neck surgery to prevent recurrent laryngeal nerve (RLN) injury. Proper positioning of the EMG tube is of paramount importance. In this study, we aimed to compare the use of video laryngoscopy with other methods for achieving the optimal depth of the EMG tube. Methods: We retrospectively enrolled 489 adult patients (with 675 nerves at risk [NAR]) undergoing surgery using the EMG endotracheal tube. Patients were categorized into three groups with: rigid laryngoscope (n = 140, NAR = 187), conventional laryngoscope (n = 262, NAR = 370), and video laryngoscope (n = 87, NAR = 118). A formula for predicting optimal depths of the EMG tube was obtained from data of the standard group with rigid laryngoscope. Depths of the EMG endotracheal tube were measured and postoperative RLN injuries were analyzed. Results: Based on linear regression, the formula was derived for predicting the optimal depth of EMG endotracheal tube (cm) = 11.028 + 0.635 * gender (female = 0; male = 1) + 0.069 * height (cm). Compared to conventional laryngoscope, intubation of EMG tube with video laryngoscope resulted in less discrepancy between its actual value and optimal value, and the tube depth was more correct (OR = 2.888, 95% CI = 1.753–4.757, p < 0.001). All five postoperative permanent RLN injuries were found in the group with conventional laryngoscope. Conclusion: EMG endotracheal tube insertion with video laryngoscopy is superior to conventional laryngoscopy, as well as an alternative to rigid laryngoscopy. The video laryngoscopy is a novel approach to get optimal depth of EMG endotracheal tube during neck surgery.